Life imprisonment in Serbia: Current legislation, theoretical issues and international legal standards - Banović, Jovana (NBP. Nauka, bezbednosti, policija, 2022)
The subject of this article is the analysis of the novelties regarding life imprisonment in the Criminal Code of Serbia that have been in force since 1 December 2019. The accent falls on the criminal law dimension of these amendments, especially based on the basic principles and their influence on the whole system according to the other provisions of positive law in Serbia. We give the reasons pro and contra life imprisonment as such and the proposal of its special forms and legal solutions (e. g. life without possibility of parole). Moreover, our review touches upon some legal and philosophical aspects that potentially occur in the adoption and implementation phase, both in the national and international law.
Keywords: life imprisonment; principles of criminal law; parole; pardon; international standards